2016
DOI: 10.1016/j.jstrokecerebrovasdis.2015.10.015
|View full text |Cite
|
Sign up to set email alerts
|

A Model for Predicting Persistent Elevation of Factor VIII among Patients with Acute Ischemic Stroke

Abstract: Background and Purpose Elevated levels of coagulation factor VIII (FVIII) may persist independent of the acute-phase response; however, this relationship has not been investigated relative to acute ischemic stroke (AIS). We examined the frequency and predictors of persistently elevated FVIII in AIS patients. Methods AIS patients admitted between July 2008 and May 2014 with elevated baseline FVIII levels and repeat FVIII levels drawn for more than 7 days postdischarge were included. The patients were dichotom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
3

Year Published

2016
2016
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 13 publications
0
4
0
3
Order By: Relevance
“…Many studies have investigated the association between FVIII and/or VWF levels and the risk of cardiovascular or cerebrovascular events ( 8 , 9 , 12 , 36 ). Despite few conflicting results, it has been well established that elevated FVIII and/or VWF levels predispose patients to AIS ( 8 , 12 ).…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have investigated the association between FVIII and/or VWF levels and the risk of cardiovascular or cerebrovascular events ( 8 , 9 , 12 , 36 ). Despite few conflicting results, it has been well established that elevated FVIII and/or VWF levels predispose patients to AIS ( 8 , 12 ).…”
Section: Discussionmentioning
confidence: 99%
“…Although FVIII has traditionally been viewed as an acute phase reactant, a recent study found that post-ischemic stroke, FVIII levels appear to remain elevated remote from index stroke in a majority of patients whose levels were elevated during the acute phase of ischemic stroke. 118 The study developed prediction models for determining which patients would experience persistently elevated FVIII at the two most commonly used activity thresholds, 150% and 200%. In both models, female sex was included as a predictor of persistent FVIII elevation.…”
Section: Specific Pathologies Predicting Ischemic Strokementioning
confidence: 99%
“…the higher the ABNR2 index, the less the activity of Factor VIII.) and existing views about the relationship between the levels of factor VIII or ATNR2 and the occurrence of a stroke [7,8,9,10]. An explanation of this phenomenon can be found in the publications [13,14], which show that the activation of FVIII causes the rapid appearance of antibodies (Factor VIII Inhibitors) that block its activity.…”
Section: Discussion Of the Medical Outcomementioning
confidence: 99%
“…At the same time, the cause of stroke is the process of thrombus formation affected by the FVIII. Its connection to the stroke risk was noted in [9,10]. In this regard, it is of interest to study the relationship between the two indicators: ABNR2 and FVIII.…”
Section: Introductionmentioning
confidence: 99%